The Nigerian rice economy: Policy options for transforming production, marketing, and trade - Gyimah-Brempong, Kwabena; Johnson, Michael E.; Takeshima, Hiroyuki (International Food Policy Research Institute, 2016)
Rice has become one of Nigeria's leading food staples. And rice consumption has outpaced production, making Nigeria the world's leading importer of rice. As a result, reducing import dependence is now a major goal of Nigerian policymakers. In The Nigerian Rice Economy the authors assess three options for reducing this dependency—tariffs and other trade policies; increasing domestic rice production; and improving post-harvest rice processing and marketing—and identify improved production and postharvest activities as the most promising. These options, however, will require substantially increased public investments in a variety of areas, including research and development, basic infrastructure (for example, irrigation, feeder roads, and electricity), and rice milling technologies. The analysis, methods used, and recommendations provided in The Nigerian Rice Economy will be equally valuable to a broad range of readers including researchers, development specialists, students, and others concerned with applications of food policy analysis and economic development more broadly in Nigeria and elsewhere in Africa south of the Sahara.